Sales Force Effectiveness: Aligning Sales Operation with the Motivation Hub - Gupta, Ritu (Indian Journal of Marketing, 2011)
Organisations continue to face the challenge of achieving and maximising sales force effectiveness. Managing the sales force is one of the most difficult jobs in sales and marketing. In part, this is because each sales person operates almost as an independent agent - there is often a fair amount of autonomy. In an effort to monitor and control the sales force, it is often necessary to monitor the sales force metrics closely. The sales team of the 21st century has to meet the needs of a fragmented marketplace. Sales operations is an emerging management discipline in firms with a strong focus on sales force productivity. Leveraging an array of support initiatives, sales operations boost sales force productivity through technology, process improvements, reporting and training. Employing the motivation hub's theoretical framework, company assigned goals (i.e. quotas), self-set goals and self-efficacy are modelled as antecedents to selling effort and new product sales. To ensure that the considerable investment required in employing and supporting a sales team is well-spent, robust mechanisms for measuring and targeting SFE are essential. There are several mechanisms available to measure SFE, which can help managers make difficult but objective resource decisions. These include benchmarking representative's performance, assessing message recall and message delivery and analytical data crunching with analysis of sales force activity. This latter mechanism is a critical element of the assessment mix. Interpreting sales data effectively is a key factor in optimising sales performance. An effective business analysis tool can help companies to measure their sales productivity and improve their effectiveness thus impacting the ROI. The aim of this research paper is to maximise Sales Force Effectiveness by aligning Sales Operations with Motivation Hub. This research paper will provide an overview of the current drivers behind the evolution of sales force effectiveness. It analyses current and emerging sales force effectiveness models. It also focuses on how to optimise sales effectiveness through a variety of medium. Further, it focuses on evaluation of key customer targeting and segmentation strategies.